2020
DOI: 10.1063/5.0015226
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a minority heating scenario in three-ion components plasma on EAST

Abstract: Heating with the wave in the ion cyclotron range of frequencies (ICRF) has been used in the development of high-performance H-mode operations in EAST. A different ion cyclotron resonance heating scenario in three-ion component plasma with real experimental parameters on EAST was investigated using a numerical tool. Excellent radio frequency wave absorption was found with an extremely low 3He concentration (0.1%–0.4%) in D-H-(3He) plasma, by adjusting the plasma composition appropriately in our simulation. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In our calculations, the initial location of fast ions is chosen to be located near the magnetic axis, but symmetrical in toroidal direction, as shown in figure 1(b). This is consistent with the results of figure 4 in [19], where it is shown that the resonance layer of the H ions is located near the magnetic axis. In the resonance layer, the fast ions are uniformly loaded in the configuration space.…”
Section: Simulation Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…In our calculations, the initial location of fast ions is chosen to be located near the magnetic axis, but symmetrical in toroidal direction, as shown in figure 1(b). This is consistent with the results of figure 4 in [19], where it is shown that the resonance layer of the H ions is located near the magnetic axis. In the resonance layer, the fast ions are uniformly loaded in the configuration space.…”
Section: Simulation Parameterssupporting
confidence: 93%
“…Here a simplification of the same effective perpendicular temperature in the whole resonance layer is adopted. The maximum ion temperature of fast ions traced in our calculation is set as 119 keV, which is chosen according to [19]. The prompt loss time is about 200 ms for the parameters used in our simulations.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To reach the ignition temperature, the auxiliary heating, such as high-energy NBI heating or resonant heating using RF waves, must supplement the intrinsic ohmic heating [1]. Ioncyclotron resonant heating (ICRH) has a variety of heating schemes [1][2][3], and it has the advantage of localized deposition of energy and the ability to heat the core plasma [4,5]. Different from the RF wave heating, NBI heating is independent on any resonance or coupling conditions [6], and its heating physical mechanism is clear and has a high plasma heating efficiency, and it can preferentially heat the electrons or ions in the background plasma as needed [7].…”
Section: Introductionmentioning
confidence: 99%